Screening Non-Saccharomyces Yeasts as Low Ethanol Producing Starter Cultures - Mehlomakulu, N.N.; Hoff, J.W.; Erten, H.; Beukes, L.; Jolly, N.P. (South African Journal of Enology and Viticulture, 2021)
Non-Saccharomyces yeasts are known for their low fermentation rate in comparison to Saccharomyces cerevisiae. In this study, non-Saccharomyces yeasts were inoculated into Chenin blanc grape must and fermented under aerobic and anaerobic conditions. Saccharomycodes ludwigii displayed a strain-dependent fermentation rate, which yielded between 5.2% and 9.9% ethanol concentration under both conditions, albeit with residual sugar. Aerobic conditions favoured the production of reduced ethanol which was between 5.8% and 9.7% for non-Saccharomyces yeasts in comparison to S. cerevisiae (10%). This trend was observed for Wickerhamomyces anomalus, Stamerella bacillaris (Candida zemplinina), Metshnikowia pulcherrima, Cyberlindnera saturnus, Wickerhamomyces subpelliculosus and Cyberlindnera jadinii. The laboratory-scale wines prepared with the aforementioned yeasts yielded ripe fruit and floral aroma attributes while other non-Saccharomyces yeasts resulted in wines with spicy, acidic and solvent aroma notes.